Implementasi Pasal 4 Peraturan Daerah Provinsi Lampung Nomor 3 Tahun 2006 Tentang Pengelolaan Sumber Daya Alam dan Lingkungan Hidup (Studi Pada Badan Pengelolaan dan Pengendalian Lingkungan Hidup Kota Bandar Lampung) - Agus Iskandar (KEADILAN PROGRESIF, 2016)
Indonesia is a unitary state with a Republican form , and the natural resources therein , should be maintained as much as possible for the prosperity of the people . In the management stages of Natural Resources and Environment , each region has authority to mengelolaa natural resources and environment, based on the principle of local autonomy . For in Lampung Province itself the management of Natural Resources and Environment is regulated through Lampung Provincial Regulation No. 3 of 2006 on the Management of Natural Resources and Environment .